The Shanghai Cooperation Organization is a regional security and economic cooperation organization. - Dilrabo JabborovaTog‘oyovna (Genius Journals, 2023)
This article analyzes the history of the formation of the Shanghai Cooperation Organization, the stages of its development, and the role and role of this organization in ensuring regional security and economic cooperation. They talked about the organization's Samarkand summit and the issues discussed there.
Keywords: Shanghai Cooperation Organization; military; political; declaration